497 The case of growth arrest which appeared to be hypothyroidism and pituatry hyperplasia. (29th October 2021) - Artcukevich, Iryna; Zenevich, O; Zhemoytiak, V; Collins, L
Abstract : Background: Normal growth is the main of all fundamental characteristics of childhood. Deviation from a normal pattern of growth plate is dependent on variety of different factors, including nonendocrine disorders and hormonal stimuli: growth hormone, IGF-I, sex steroids, thyroid hormones, paracrine growth factors, and cytokines. Case: We present 12 years old girl who was referred to endocrinology department (she had reduced of the height velocity in the last 3 years old and appeared overweight . The girl was born by the first normal pregnancy. Her birth weight was 3.8 kg, length 54 cm. Her intellectual development and school performance was good. She did not have any complains. Her weight was 32kg (10–25 centile), and height 114 cm (<3 centile), BMI 98th centile The skin was dry and pale. The test showed TSH – 820 mIU/L, T4f – 1.51 mIU/L, and elevated antithyroperoxidase antibodies level. The US of the thyroid gland showed the reduced of the echogenic structure and multiple heterogeneous structures, confirming The Primary Hypothyroidism due to Autoimmune thyroiditis. MRI head reported The Pituitary Hyperplasia/Pituitary Adenoma secondary to The Primary Hypothyroidism. She was commenced on levothyroxine 50μg/kg once daily. The repeated test after 10 days of treatment showed TSH 448.4 mIU/L T3 2.49 mIU/L, T4 7.15 mIU/L. She was discharged home on levothyroxine and regular monitoring of TSH. Conclusion: Thyroid hormone is a major contributor to postnatal growth and hypothyroidism occurring postnatally can result in profound growth failure and arrest of skeletal maturation. The danger of chronic autoimmune thyroiditis disease lies in the fact that the disease is almost asymptomatic. Pituitary hyperplasia usually developed due to hypothyroidism, that responds well to thyroid hormone replacement therapy.